THE OPTIMIZATION OF PUMP TYPE HYDRAULIC PUMPING UNIT BY REDESIGNING WELL SB-02 AT PT SMD TAMPI FIELD - Sefilra Andalucia; Moh. Riza Zakaria; Rendi Sahputra (Jurnal Cakrawala Ilmiah, 2023)
Production is an activity to transport hydrocarbon fluids from the subsurface (reservoir) to the surface. To increase the productivity of a Hydraulic Pump Unit, it is necessary to pay attention to pump production capacity, stroke length, pumping speed. A decrease in pump production can be caused by a variety of factors. This study aims to evaluate the possibility of increasing production in the study well by redesigning the Hydraulic Pump Unit in order to achieve optimum volumetric efficiency in the SB-02 Well in the Lampi Field. In this study, the data processing method by evaluating the installed pump and calculating the evaluation of the installed pump then calculating the volumetric efficiency of the pump if the production of SB-02 Well has not reached the specified target, it is necessary to optimize it. Based on dynagraph analysis, it is known that there is damage in the pump, namely in the fluid pound, so that the pump can be optimized by changing the pump parameters. HPU pump optimization is making an IPR Curve using the Darcy Method, because the water cut is only 1%. The optimization method was doing to change the pump parameters, namely pump stroke speed (SPM) and pump stroke length (SL). To get the optimal combination of pump parameters is done by nodal analysis (Pump Intake Curve). The redesign of the HPU pump optimization method is to change the pump stroke speed from 10 SPM to 9 SPM, Fixed Stroke Length which is 80 inches. After optimization was carried out on the SB-02 Well, the result obtained was an increase in the volumetric efficiency of the installed pump. The volumetric efficiency of the previously installed pump was 58.25% to 75.45%, the increase in production flow rate (Qt) from SB-02 Well was 32.90 bfpd, with the previous flow rate of 217.10 bfpd rising to 250 bfpd.